2018
DOI: 10.1007/s40620-018-0507-1
|View full text |Cite
|
Sign up to set email alerts
|

Sodium removal by peritoneal dialysis: a systematic review and meta-analysis

Abstract: Achievement of sodium and fluid balance is considered a major determinant of dialysis adequacy in peritoneal dialysis (PD). However, the contribution of different PD modalities to dialytic sodium removal (DSR) remains ill-defined. We performed a systematic review and meta-analysis to compare DSR by manual (continuous ambulatory PD, CAPD) versus automated PD (APD). Alternative PD strategies to remove sodium were also analyzed. Seven cohort studies, including 683 patients, 406 in CAPD and 277 in APD, were meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 57 publications
0
23
2
3
Order By: Relevance
“…While we expect no difference in sodium removal between the regimens, we do however expect a lower sodium removal in APD with respect to CAPD, mainly due to the shorter dwell times involved. Indeed, a recent meta-analysis including 683 patients showed that CAPD offers a higher sodium removal than APD even though UF is not different [8].…”
Section: Discussionmentioning
confidence: 99%
“…While we expect no difference in sodium removal between the regimens, we do however expect a lower sodium removal in APD with respect to CAPD, mainly due to the shorter dwell times involved. Indeed, a recent meta-analysis including 683 patients showed that CAPD offers a higher sodium removal than APD even though UF is not different [8].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, salt restriction remains the basic approach to achieve volume control in PD patients, keeping in mind that sodium removal is lower in PD patients treated with cycler (Automated PD, APD), because of greater sodium sieving as compared with Continuous Ambulatory PD (CAPD). In these patients, high salt intake may not be counterbalanced by sodium removal, consequently leading to hypervolemia and hypertension [88].…”
Section: Sodium Intake In End-stage Kidney Diseasementioning
confidence: 99%
“…The results of this study can be in part explained by the fact that almost 80% of the APD patients received icodextrin for their long daytime dwell, and the number of nocturnal exchanges were reduced (i.e., allowing for longer dwells and less sodium sieving). Nevertheless, a recent meta-analysis including 683 patients from 7 studies concluded that CAPD is associated with significantly higher SR compared with APD (141 vs. 86 mmol/day, respectively, p = 0.015) [20]. Since APD is the predominant modality in many countries, a number of investigators have explored methods (i.e., tidal APD and mid-day exchange) to enhance its SR capability rather than switching to CAPD.…”
Section: Pd Modalitiesmentioning
confidence: 99%
“…The correlation between ultrafiltration volume and sodium extraction could be more pronounced in patients treated with CAPD than APD (possibly due to a higher proportion of the ultrafiltrate volume being from the sodium-free water in APD) [20]. …”
Section: Ultrafiltration Volume and Posturementioning
confidence: 99%